THROUGH ATTRACTION TO THE DETERRENCE – ISSUES AND POSSIBILITIES OF THE WESTERN BALKAN COUNTRIES - Subotic, Milovan (Serbian political thought, 2023)
The inevitable security paradigm shift is the special focus of so-called small states and regions with multitude if fundamental cultural and general identity features that are represented as insurmountable. Thirty-year period of existence of new states on the post-Yugoslav area has been marked with misunderstandings and conflicts, which caused the need for deterring each other from another one, or rather everyone from everyone. The Western Balkans is a blatant example of security sensitive region where military approach to problem-solving often was a preference over all the other elements from the so-called civil action. That is why, by inertia, the domain of enhancing military power in the region is considered as the key (some would say the only) factor of deterrence from the other one, different, and threatening. Who is being deterred, from whom, and with what, in the complex security paradigm of the Western Balkans region? Is it time for the countries of the region to break the chain of vicious circle of indefinitely frozen conflicts, and what are the ways for the change of the deterrence perception in this region, are some of the research questions this paper is trying to answer. Likewise, the paper is analyzing the reach of the economic integrations of the Western Balkan countries, as ‘tools’ for the reduction of tensions and deactivation of omnipresent security dilemmas. The importance of “Open Balkan” initiative is specifically analyzed because of its potential for additional connection of present member states, but also as a capacity for attraction of other regional countries. Thus, the elimination of security dilemmas (and eventually the elimination of threats) between the Western Balkan countries would present the result of the attraction as the most constructive category in strategic deterrence. The chance that the Republic of Serbia has (again) – to replace the role of decades long deterrence factor with the progressive one, attraction – should not be missed. Key words: deterrence, attraction, Western Balkans, threat, conflicts, Open Balkan, economy, future.
Keywords: deterrence, attraction, Western Balkans, threat, conflicts, Open Balkan, economy, future.